Analysis Principal’s Performance in Managing Human Resources at SMK Negeri 1 Gunungsitoli Utara - Ziliwu, Syukur Idaman; Harefa, Trisman; Zega, Riswan; Harefa, Afore Tahir (ITScience (Information Technology and Science), 2024)
The performance of school principal in managing human resources involves efforts to develop and utilize the potential of teaching and educational staff effectively to achieve educational goals. This research aimed to analyze the performance of the principal in managing human resources and the principal's efforts in improving the skills of English teachers at SMK Negeri 1 Gunungsitoli Utara. The research method used was a qualitative method with a descriptive approach. Data were collected through direct observation and structured interviews with the school principal and two teachers. The research results showed that school principal demonstrated good managerial competence in three main aspects: leadership, management of teacher and staff human resources, student management. The principal was success in leading meetings effectively, providing clear direction, and motivating teachers and staff for professional development. In managing human resources, school principal routinely carry out performance assessments, prepared efficient work schedules, and encouraged staff participation in decision making. In the field of student management, the principal was success in managing the admission of new students, placing students according to their abilities, and apart from that, the principal also provided teachers' needs such as books, dictionaries and moreover the principal gives teachers the freedom to increase their potential independently and also implemented MGMP (Musyawarah Guru Mata Pelajaran) as an effort to improve the skills of English teachers. The school principal demonstrated strong leadership, effective human resource management, and successful student management.